The impact of Sejingkat coal-fired power plant on the water quality of Sarawak River - Anita, Bruin (Universiti Malaysia Sarawak (UNIMAS), 2006)
The demand for electricity is clearly associated with population growth. Thus, the Kuching Coal-Fired Power Plant located at Sejingkat area was built to cater for this needs. With the operation of Phase II, the impact to the water quality of the Sarawak River is not known. In view of this fact, studies have been conducted to evaluate the water quality on the affected river. Generally, the result obtained in this study showed that the river was classified under Class II during mid high tide and Class III during low tide (wQI) which is good and moderate respectively. However, parameter such as turbidity was outside any of the Class listed (INQWS). Meanwhile, during low tide parameters such as temperature increased slightly from 31.9 to 34.7 °C whereas pH value decreased slightly from 7.9 to 7.6 as compared to the condition when only Phase I was in operation. The other parameters such as TSS, BOD and COD were within Class II while parameters such as DO, ammoniacal-nitrogen, nitrate-nitrogen and orthophosphate were within Class III in accordance with INWQS. Thus, it is still viable to support the aquatic life.